Inverted CD8 T-Cell Exhaustion and Co-Stimulation Marker Balance Differentiate Aviremic HIV-2-Infected From Seronegative Individuals - Scharf, Lydia; Pedersen, Christina B.; Johansson, Emil; Lindman, Jacob; Olsen, Lars R.; Buggert, Marcus; Wilhelmson, Sten; Månsson, Fredrik; Esbjörnsson, Joakim; Biague, Antonio; Medstrand, Patrik; Norrgren, Hans; et al. (Frontiers in Immunology, 2021)
HIV-2 is less pathogenic compared to HIV-1. Still, disease progression may develop in aviremic HIV-2 infection, but the driving forces and mechanisms behind such development are unclear. Here, we aimed to reveal the immunophenotypic pattern associated with CD8 T-cell pathology in HIV-2 infection, in relation to viremia and markers of disease progression. The relationships between pathological differences of the CD8 T-cell memory population and viremia were analyzed in blood samples obtained from an occupational cohort in Guinea-Bissau, including HIV-2 viremic and aviremic individuals. For comparison, samples from HIV-1- or dually HIV-1/2-infected and seronegative individuals were obtained from the same cohort. CD8 T-cell exhaustion was evaluated by the combined expression patterns of activation, stimulatory and inhibitory immune checkpoint markers analyzed using multicolor flow cytometry and advanced bioinformatics. Unsupervised multidimensional clustering analysis identified a cluster of late differentiated CD8 T-cells expressing activation (CD38+, HLA-DRint/high), co-stimulatory (CD226+/-), and immune inhibitory (2B4+, PD-1high, TIGIThigh) markers that distinguished aviremic from viremic HIV-2, and treated from untreated HIV-1-infected individuals. This CD8 T-cell population displayed close correlations to CD4%, viremia, and plasma levels of IP-10, sCD14 and beta-2 microglobulin in HIV-2 infection. Detailed analysis revealed that aviremic HIV-2-infected individuals had higher frequencies of exhausted TIGIT+ CD8 T-cell populations lacking CD226, while reduced percentage of stimulation-receptive TIGIT-CD226+ CD8 T-cells, compared to seronegative individuals. Our results suggest that HIV-2 infection, independent of viremia, skews CD8 T-cells towards exhaustion and reduced co-stimulation readiness. Further knowledge on CD8 T-cell phenotypes might provide help in therapy monitoring and identification of immunotherapy targets.